Myricitrin, a Glycosyloxyflavone in Myrica esculenta Bark Ameliorates Diabetic Nephropathy via Improving Glycemic Status, Reducing Oxidative Stress, and Suppressing Inflammation - Tarun K. Dua; Swarnalata Joardar; Pratik Chakraborty; Shovonlal Bhowmick; Achintya Saha; Vincenzo De Feo; Saikat Dewanjee (Molecules, 2021)
The present study evaluated the therapeutic potential of myricitrin (Myr), a glycosyloxyflavone extracted from Myrica esculenta bark, against diabetic nephropathy. Myr exhibited a significant hypoglycemic effect in high fat-fed and a single low-dose streptozotocin-induced type 2 diabetic (T2D) rats. Myr was found to improve glucose uptake by the skeletal muscle via activating IRS-1/PI3K/Akt/GLUT4 signaling in vitro and in vivo. Myr significantly attenuated high glucose (HG)-induced toxicity in NRK cells and in the kidneys of T2D rats. In this study, hyperglycemia caused nephrotoxicity via endorsing oxidative stress and inflammation resulting in the induction of apoptosis, fibrosis, and inflammatory damages. Myr was found to attenuate oxidative stress via scavenging/neutralizing oxidative radicals and improving endogenous redox defense through Nrf-2 activation in both in vitro and in vivo systems. Myr was also found to attenuate diabetes-triggered renal inflammation via suppressing NF-κB activation. Myr inhibited hyperglycemia-induced apoptosis and fibrosis in renal cells evidenced by the changes in the expressions of the apoptotic and fibrotic factors. The molecular docking predicted the interactions between Myr and different signal proteins. An in silico absorption, distribution, metabolism, excretion, and toxicity (ADMET) study predicted the drug-likeness character of Myr. Results suggested the possibility of Myr to be a potential therapeutic agent for diabetic nephropathy in the future.